Ginkgo Biloba: plant applications for memory disorders - Valente, Caroline (2021)
This article aims to show an analysis the plant Ginkgo biloba, which has been used for memory disorders. Performed a literature review through materials published in the SciELO, LILACS and MEDLINEdatabases. It was selected and synthesized in a table eight works that used Ginkgo bilobarelated to memory, aging and alzheimer's disease. It was found that, in this herbal medicine, flavonoids are attributed to antioxidant and anti-free radical actions,thus acting to increase blood flow, protecting against damage caused by hypoxia, inhibiting platelet aggregation. Therefore, it was noticed in this work that Ginkgo bilobais widely used worldwide, especially by individuals who want to delay the effects of aging, because due to its application in a number of diseases, particularly with memory disorders, its function is preventive and/or curative, generating information that will be evidenced, making clear the confirmation of its effectiveness by tradition of use.